PEDAGOGIK KOLABORATIF SEBAGAI SOLUSI PEMBELAJARAN ABAD 21 - Halimah, Siti; Babang Robandi; Eti Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
21st century learning demands significant changes in pedagogical approaches to adapt to the demands of a dynamic, technology-based world. Collaborative pedagogy, which emphasizes cooperation between students, teachers and other parties, is one solution to achieve this. This article discusses the meaning and application of collaborative pedagogy, its impact on students' critical and social skills, and the challenges faced in its implementation at various levels of education. By analyzing several empirical studies both at home and abroad, this article aims to show the importance of collaborative pedagogy in 21st century learning. In addition, this article also identifies several factors that can influence the effectiveness of implementing collaborative pedagogy, such as teacher readiness, technological infrastructure, and education policy support. Based on the results of the study, collaborative learning has been proven to be able to improve students' critical thinking skills, creativity and social abilities, all of which are very much needed in life in the digital age. Thus, collaborative pedagogy is not only a relevant pedagogical approach, but also essential for preparing young people to face future challenges.